Clumpy Novel Mitochondrial Signatures in Irradiated Human Diabetic Buccal Cells: A Case Control Study - Surraj SUSAI; Mrudula CHANDRUPATLA; Sumitra SIVAKOTI; Govindrao N. KUSNENIWAR; Anand K. PYATI (Medeniyet Medical Journal, 2025)
Objective: This study aimed to determine the whole free mitochondria in type-2 diabetic buccal epithelial cells using a supravital stain called 'Janus Green B' and assess their behavior after exposure to near infrared light. The researchers observed microscopic mitochondrial load and its intracellular spatial behavior after exposure to near-infrared rays, bridging the gap in understanding mitochondrial orientation in diseases like diabetes. The aim of this research was to find out the quantitative involvement and electrostatic intracellular spatial patterns of whole mitochondria in diabetes. Methods: Exfoliated buccal cell wet mounts, supravitally stained using Janus green, and excited using infrared rays, were observed using an advanced bright field Axiocam microscope, and the images of whole mitochondria within the cells were photographed and analyzed using the ZEN 2.0 cell sense software. The migration patterns of mitochondria were observed. Results: A quantitative decrease in mitochondria was noted in diabetic cells. Signatures of clumpy peripheral shifts in mitochondria were observed in diabetic buccal cells post radiation. Conclusions: Advanced glycation end products of diabetes combined with oxidative stressors influenced the free mitochondria to clump peripherally and produce a characteristic signature. The decreased mitochondrial load contributed additional evidence to the reduced respiratory capacity of cells, which forced mitochondria to emit a detectable signature when irradiated.